Exploring the Impact of Social Media on the Integration of Western Cultural Elements by University Students in China - Xinran Li; Meihua Liu; Chen Su (Studies in Social Science & Humanities, 2024)
This paper delves into the profound impact of social media on the cultural dynamics of Chinese university students, with a particular emphasis on how these digital landscapes mediate the integration, adaptation, and at times, resistance to Western cultural elements. As digital platforms become increasingly central to daily life, they not only serve as conduits for global cultural exchange but also as arenas where cultural identities are negotiated and redefined. By conducting a comprehensive analysis of popular social media platforms among Chinese youth, such as Weibo, WeChat, and Douyin, this study uncovers the complex interplay between global cultural flows and local traditions. It examines how these interactions influence the formation of identity, the evolution of values, and the adoption of social practices among the youth in China. The investigation reveals that while social media facilitates the exposure to and engagement with Western culture, Chinese university students approach these encounters with a critical eye, selectively adopting elements that resonate with their personal and cultural identity while resisting those that conflict with traditional values. This selective engagement highlights a dynamic process of cultural hybridization, where Western influences are not merely absorbed passively but are actively interpreted, modified, and integrated into the fabric of Chinese youth culture. The findings underscore the role of social media as a significant force in shaping contemporary cultural landscapes, offering insights into the broader implications of digital technology on cultural globalization and identity formation in the context of China’s rapidly changing society.